예비교사의 인공지능 전문성 신장 사례 연구 - 박정호(Jung-ho Park) (한국정보통신학회논문지, 2024)
제4차산업혁명시대의 핵심 기술 도구인 인공지능은 산업, 경제, 문화를 넘어 교육부문에도 활발히 적용되고 있다. 미래사회에서는 인공지능 기술을 이해하고, 활용하는 것은 모든 사람에게 필수적인 소양으로 여겨지고 있으며 또한,미래 인재 양성을 위한 예비 교사들의 AI교육 전문성도 중요시되고 있다. 본 연구는 예비교사의 AI교육 전문성 신장을 위해 15주 동안 AI 소양(10주), AI 융합(3주), 모의수업(2주)으로 이어지는 신장 프로그램을 적용한 후 효과성 검증을 실시하였다. 연구 결과는 다음과 같다. 첫째, AI에 대한 긍정적 인식 변화가 나타났으며(p<.05). 둘째, 교과연계프로그램 개발을 AI 교육기술도구에 대한 이해가 향상되었으며, 긍정적인 사용과 유용성을 갖게 되었다. 셋째, 마이크로 티칭을 통해 교사의 역량 개발의 중요성을 알게되고, 학생의 학습과정에 대한 이해가 확장되었다. Artificial intelligence, a key technological tool in the era of the 4th Industrial Revolution, is being actively applied toeducation beyond industry, economy, and culture. In the future society, understanding and using artificial intelligencetechnology will be considered an essential skill for everyone, and the professionalism of AI education for pre-serviceteachers nurturing future talents is also important. This study verifies the effectiveness of pre-service teachers afterundergoing a 15-week extension program consisting of AI Literacy Education (10 weeks), AI-Linked Subjet Education (3weeks), and Micro-teaching (2 weeks) which was designed to enhance the AI ​​education professionalism of pre-serviceteachers. The study results are as follows. First, there was a change in the positive perception of AI (p<.05). Second, theunderstanding of AI educational technology tools was improved and the recognition of the usefulness of developing acurriculum-related program was expanded. Third, the importance of teacher competency development was learned throughthe micro-teaching, and the students' understanding of the learning process was expanded. KCI Citation Count: 2